Comparison of bioactive constituents by HPLC-DAD-ESI-MS and UFLC and in vitro antioxidant activities of blossom honey, bee pollen, and propolis - Saroglu, Oeznur; Bayram, Nesrin Ecem; Ozcelik, Beraat (SPRINGER, 2023)
The aim of this study was to analyze the total phenolic content, phenolic profile, and antioxidant activity of honey, bee pollen, and propolis samples from Turkey's Black Sea Region. The total phenolic content of these bee products was found using Folin-Ciocalteu's method, and their antioxidant capacity was found using the 2,2-diphenyl-1-picrylhydrazyl (DPPH) and cupric ion reducing antioxidant capacity (CUPRAC) assays. Phenolic compounds of honey samples were characterized by high-performance liquid chromatography coupled to a photodiode array detector and mass spectrometer (HPLC-DAD-ESI-MS), while phenolic compounds of bee pollen and propolis samples were quantified ultra-fast liquid chromatography (UFLC). The total phenolic values for honey, bee pollen and propolis were 6.32-18.21 mg GAE/100 g, 547.64-769.4 mg GAE/100 gr, and 6096.1-11,564 mg GAE/100 gr, respectively. DPPH and CUPRAC values of honey, pollen and propolis were 11.05-21.38% and 0.38-1.48 & mu;mol Trolox/g; 24.67-38.63% and 0.03-0.05 mmol Trolox/g; 11.81-34.12% and 0.47-0.89 mmol Trolox/g, respectively. About 30 different phenolic compounds were identified as quantitative. Our findings have shown that all bee products examined in the study are found to contain gallic acid, naringenin, and caffeic acid. In terms of total phenolic content and antioxidant activity, the bee product extracts were ranked as follows: propolis > bee pollen > honey. The high concentration of phenolic compounds in propolis explains its remarkable antioxidant effect.
Keywords: Honey; Propolis; Bee pollen; Antioxidant activity; Phenolic compounds; PHENOLIC PROFILE; PHYSICOCHEMICAL PROPERTIES; RED PROPOLIS; CHEMICAL-COMPOSITION; FLORAL ORIGIN; VITAMIN-C; EXTRACT; ANTIBACTERIAL; CAPACITY; ACID; Food Science & Technology